COVID-19, Social Justice, and Clinical Cancer Research. (15th October 2020) - Doroshow, James H; Prindiville, Sheila; McCaskill-Stevens, Worta; Mooney, Margaret; Loehrer, Patrick J
Abstract: The coronavirus disease 2019 (COVID-19) pandemic and related socioeconomic events have markedly changed the environment in which cancer clinical trials are conducted. These events have resulted in a substantial, immediate-term decrease in accrual to both diagnostic and therapeutic cancer investigations as well as substantive alterations in patterns of oncologic care. The sponsors of clinical trials, including the US National Cancer Institute, as well as the cancer centers and community oncology practices that conduct such studies, have all markedly adapted their models of care, usage of healthcare personnel, and regulatory requirements in the attempt to continue clinical cancer investigations while maintaining high levels of patient safety. In doing so, major changes in clinical trials practice have been embraced nationwide. There is a growing consensus that the regulatory and clinical research process alterations that have been adopted in response to the pandemic (such as the use of telemedicine visits to reduce patient travel requirements and the application of remote informed consent procedures) should be implemented long term. The COVID-19 outbreak has also refocused the oncologic clinical trials community on the need to bring clinical trials closer to patients by dramatically enhancing clinical trial access, especially for minority and underserved communities that have been disproportionately affected by the pandemic. In this commentary, changes to the program of clinical trials supported by the National Cancer Institute that could improve clinical trial availability, effectiveness, and diversity are proposed.